Nonlinear analysis of concrete-filled steel square tube strengthened by internal transverse stiffened bars under axial compression - Nan Li; Lai Wang; Yajun Xi; Tong Guan; Hui Wang; Furui Dong (Functional Materials, 2017)
A new type of concrete-filled square steel tubular(CFSST) column is proposed, which is characterized by the transverse stiffened steel bars arranged inside the pipe wall to improve confinement performance of the concrete core. This paper employs a nonlinear analysis of square CFSST stub columns under axial compression. A three-dimensional nonlinear finite element (FE) model is developed using ABAQUS, where nonlinear material behavior and enhanced strength corner properties of steel are included. Close agreement is achieved between the test and FE results in terms of load-deformation response and ultimate strength.